How do you solve 7x - 10= - 6x ^ { 2}7x10=6x2?

2 Answers
Sep 22, 2017

Use the quadratic formula.

Explanation:

First, rearrange the equation to match the form ax^2 + bx + c = 0ax2+bx+c=0

6x^2 + 7x - 10 = 06x2+7x10=0

a= 6a=6
b = 7b=7
c = -10c=10

Then using the quadratic formula: x = (-b+-sqrt(b^2 - 4ac))/(2a)x=b±b24ac2a
Substitute in the numbers:

x = (-7+-sqrt(7^2 - 4(6*-10)))/(2*6)x=7±724(610)26

and simplify:

x = (-7+-sqrt(289))/(12)x=7±28912

x = (-7+-17)/(12)x=7±1712

So your two solutions would be:

x = 5/6x=56 and x = -2x=2

Sep 22, 2017

7x-10=-6x^27x10=6x2

6x^2+7x-10=06x2+7x10=0

6x^2+12x-5x-10=06x2+12x5x10=0

6x*(x+2)-5*(x+2)=06x(x+2)5(x+2)=0

(6x-5)*(x+2)=0(6x5)(x+2)=0

Hence x_1=5/6x1=56 and x_2=-2x2=2

Explanation:

1) I transferred squared term to left side.

2) I decomposed polynomial using common multiplier.

3) I solved each multiplier.